2017
DOI: 10.1111/1471-0528.14774
|View full text |Cite
|
Sign up to set email alerts
|

Audit and feedback using the Robson classification to reduce caesarean section rates: a systematic review

Abstract: BackgroundIn most regions worldwide, caesarean section (CS) rates are increasing. In these settings, new strategies are needed to reduce CS rates.ObjectivesTo identify, critically appraise and synthesise studies using the Robson classification as a system to categorise and analyse data in clinical audit cycles to reduce CS rates.Search strategyMedline, Embase, CINAHL and LILACS were searched from 2001 to 2016.Selection criteriaStudies reporting use of the Robson classification to categorise and analyse data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 29 publications
0
47
2
8
Order By: Relevance
“…This is evident from its recent widespread use in systematic reviews and clinical audits. 1,11 Boatin et al in their systematic review concluded that Robson provides a stable framework, both alone and in conjunction with other approaches for categorizing and analyzing data in audit cycles. 1 Several authors have sub classified Robson so that the circumstances that lead to a CS in a particular class can be well elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is evident from its recent widespread use in systematic reviews and clinical audits. 1,11 Boatin et al in their systematic review concluded that Robson provides a stable framework, both alone and in conjunction with other approaches for categorizing and analyzing data in audit cycles. 1 Several authors have sub classified Robson so that the circumstances that lead to a CS in a particular class can be well elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 Boatin et al in their systematic review concluded that Robson provides a stable framework, both alone and in conjunction with other approaches for categorizing and analyzing data in audit cycles. 1 Several authors have sub classified Robson so that the circumstances that lead to a CS in a particular class can be well elucidated. 12,13 This audit also used the modified Robson criteria as it maintains the essence of Robson apart from demonstrating additional information for most of the classes of Robson.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the present study was the first to use a combination of audit and the TGCS for assessing the appropriateness of cesarean delivery in settings within Iran where this mode of delivery is considered to be overused. This combination offered a logical framework to analyze and understand cesarean delivery appropriateness and its impact on maternal health outcomes . Moreover, the audit comparison between Iranian and Swedish professionals was an original idea to illustrate the marked variation in obstetric decision making in countries with high and low rates of cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean deliveries, specifically those performed in low‐risk obstetric populations, could result in MNM, and without a medically justifiable indication, can be a harmful choice in childbirth. The Robson classification and audits are valuable tools in tackling questionable indications for cesarean delivery, and they can be used to improve the appropriateness and therefore lower the rates of cesarean delivery . To keep childbirth as safe as possible, cesarean delivery should only be performed when clear maternal and perinatal health benefits exist.…”
Section: Discussionmentioning
confidence: 99%